Effectiveness of product photography in improving consumer engagement on digital media platforms - Erni Masdupi; Tri Kurniawati; Halkadri Fitra; Dini Faisal (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study aimed to analyze the improvement of product photography knowledge and skills among craftsmen and partners of the Pinjaik Patah Embroidery Gallery, BUMNag Panampuang Saiyo, Agam Regency, West Sumatra, following product photography training for digital marketing purposes. A qualitative descriptive approach was employed. Data were collected through direct interviews, observation, and documentation of product photographs before and after the training. The evaluation focused on three key aspects of product photography, namely lighting and contrast, background selection, and object arrangement and composition. Product photographs published on the gallery’s Instagram account were used as the primary evidence of skill development. The findings revealed improvements in participants’ understanding and application of product photography techniques. Post-training photographs demonstrated better lighting utilization, stronger visual contrast, more consistent background selection, and improved photo composition, resulting in more attractive and persuasive product presentations for digital marketing. Product photography training effectively enhanced the basic competencies of MSME craftsmen and partners, enabling them to produce higher-quality visual content and strengthen their digital marketing performance through social media platforms.